LPAIV H9N2 Drives the Differential Expression of Goose Interferons and Proinflammatory Cytokines in Both In Vitro and In Vivo Studies - Zhou, Hao; Chen, Shun; Yan, Bing; Chen, Hongjun; Wang, Mingshu; Jia, Renyong; Zhu, Dekang; Liu, Mafeng; Liu, Fei; Yang, Qiao; Wu, Ying; Sun, Kunfeng; et al. (Frontiers in Microbiology, 2016)
Geese, as aquatic birds, are an important natural reservoir of avian influenza virus (AIV). To characterize the innate antiviral immune response against AIV H9N2 strain infection in geese as well as the probable relationship between the expression of immune-related genes and the distribution of viral antigens, we investigated the levels of immune-related gene transcription both in AIV H9N2 strain-infected geese and in vitro. The patterns of viral location and the tissue distribution of CD4- and CD8α-positive cells were concurrently detected by immunohistochemical staining, which revealed respiratory and digestive organs as the primary sites of antigen-positive signals. Average AIV H9N2 viral loads were detected in the faeces, Harderian gland and trachea, where higher copy numbers were detected compared with the rectum. Our results suggested the strong induction of proinflammatory cytokine expression compared with interferons (IFNs). Notably, in most tissues from the AIV H9N2 strain-infected birds, IFNα and IFNγ gene transcripts were differentially expressed. However, inverse changes in IFNα and IFNγ expression after AIV H9N2 strain infection were observed in vitro. Taken together, the results suggest that AIV H9N2 is widely distributed in multiple tissues, efficiently induces inflammatory cytokines in the Harderian gland and spleen of goslings and inversely influences type I and II IFN expression both in vivo and in vitro. The findings of this study further our understanding of host defence mechanisms and the pathogenesis of the H9N2 influenza virus in geese.